Recent Evidence on the Role of Dietary PUFAs in Cancer Development and Prevention - D'Archivio, Massimo; Scazzocchio, Beatrice; Vari, Rosaria; Santangelo, Carmela; Giovannini, Claudio; Masella, Roberta (Current Medicinal Chemistry, 2018)
Background: Scientific evidence has been accumulated about the effects of polyunsaturated fatty acids (PUFAs) on human health. The hypothesis that n-3 PUFAs might improve the efficiency of anticancer drugs has recently been considered. The role of n-6 PUFAs, in contrast, needs to be better assessed. However, the effective mechanisms of action of PUFAs have not been fully clarified yet. This review aims to report the most updated evidence on the role of n-6 and n-3 PUFAs in the development and treatment of human cancers, focusing on the potential mechanisms by which PUFAs exert their effects. Methods: We undertook a structured search in PubMed on February 17th 2017 for peer-reviewed research articles published from 2013. The search syntax used was: PUFA or PUFAs and cancer. Results: Contradictory results were found, most likely due to the genetic background, the different dietary sources used, the interaction among different nutrients, and the tumor subtypes. However, the more recent findings strongly support the use of n-3 PUFAs in cancer prevention and treatment. On the other hand, n-6 PUFAs are often associated with an increased risk of cancer, even if recently their beneficial effects have also been highlighted. Conclusion: N-3 PUFAs may represent a potential therapeutic agent contributing to treat at least some type of human cancers. However, studies with larger sample sizes and longer follow-up times are still needed. To increase the knowledge about how food and nutrition can improve human health it is advisable to deliver an open access nutritional database.
Keywords: human health